2016
DOI: 10.1016/j.ijgo.2016.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Community survey on awareness and use of obstetric ultrasonography in rural Sarlahi District, Nepal

Abstract: Objective To assess levels of awareness and use of obstetric ultrasonography in rural Nepal. Methods Between March 2014 and March 2015, a cross-sectional survey was conducted among married women aged 15–40 years residing in rural Sarlahi District, Nepal, regarding their knowledge and use of obstetric ultrasonography during their most recent pregnancy. Regression analyses were used to identify reproductive health, socioeconomic, and other characteristics that increased the likelihood of undergoing an obstetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…In the same study, 2.6% of respondents had ever requested fetal sex determination and when the female sex of the fetus was disclosed, over 63% of them were aborted [ 9 , 41 ]. In a study in Nepal, 6.8% of surveyed pregnant women received ultrasound exams for fetal sex determination despite it being unlawful [ 42 ]. The study also found that compared to women who had at least one live born son prior to the recent pregnancy, women with no live born sons and three or more live born daughters had 1.55 higher odds of receiving an ultrasound exam, which may suggest use for fetal sex determination [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same study, 2.6% of respondents had ever requested fetal sex determination and when the female sex of the fetus was disclosed, over 63% of them were aborted [ 9 , 41 ]. In a study in Nepal, 6.8% of surveyed pregnant women received ultrasound exams for fetal sex determination despite it being unlawful [ 42 ]. The study also found that compared to women who had at least one live born son prior to the recent pregnancy, women with no live born sons and three or more live born daughters had 1.55 higher odds of receiving an ultrasound exam, which may suggest use for fetal sex determination [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a study in Nepal, 6.8% of surveyed pregnant women received ultrasound exams for fetal sex determination despite it being unlawful [ 42 ]. The study also found that compared to women who had at least one live born son prior to the recent pregnancy, women with no live born sons and three or more live born daughters had 1.55 higher odds of receiving an ultrasound exam, which may suggest use for fetal sex determination [ 42 ]. Other popular reasons for determining fetal sex were reported to be curiosity and preparation for the baby [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The high risk associated with malpresentation underlies the value of tertiary care, but the impracticality of the recommendation shone through the experiences of numerous women. Some facilities in this area abide by a blanket referral protocol for non-cephalic presentation as reported elsewhere [ 14 ] and hinted by interviewees, but the arduousness of completing that referral puts into question the clinical value. Both lower-level clinicians and families face the reality of the risk associated with the lower capacity available in greater proximity and the risk associated with the journey for tertiary care, without a guarantee of timely and high quality care.…”
Section: Discussionmentioning
confidence: 99%
“…This issue also applies to the value of diagnostics. Most women interviewed for the study were unaware of the condition prior to delivery, which was triangulated through quantitative data [ 14 ]. Ultrasonography is the only gold standard method of detecting non-cephalic presentation prior to delivery, and access and utilization are sparse in low-resource settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation